Prarancangan Pabrik Etilen Glikol dari Etilen Oksida dan Air dengan Proses Hidrasi Non Katalitik Kapasitas 220.000 Ton/Tahun - Three Wiji Latifah, Ayu, Rois Fathoni, S.T. M.Sc. Ph.D, Ir. Herry Purnama, M.T., Ph.D (2015)
Ethylene glycol or EG is an organic compound that is colorless, odorless, and intangible fluid. Generally, ethylene glycol is used for extra fiber in polyester, materials of PET containers, antifreeze and coolant in the engine. In Indonesia generally and commercial, ethylene glycol is used as raw material for the textile industry (polyester) as much as 97.34% and 2.66% is used as raw materials for the manufacture of paints addition, liquid glue, solvent , printing ink , the ink for pen, cosmetics, and anti-freeze materials. This need fill by PT Polychem Tbk, while shortcoming fill by importing from different countries. Plant design of ethylene glycol plant from ethylene oxide and water with non-catalytic hydration process capacity of 220,000 tons/year is planned to be established in 2025 to meet the needs of ethylene glycol in Indonesia, there by reducing the number of imports. Besides the raw materials and the location in Tangerang, Banten area of 22,000m2 and with 184 employees strongly supports the establishment of this factory. Plant design ethylene glycol from ethylene oxide and excess water, with a mole ratio of 1:20. Production capacity of 220,000 tons /year is planned to operate for 330 days per year. The process of making ethylene glycol is carried out in a plug flow reactor continuously without using a catalyst. In the reactor, the process of making ethylene glycol maintained that take place in the liquid phase, irreversible, exothermic, and non-isothermal adiabatic temperature and pressure 190C-130,34C up to 18 atm. Conversion achieved was 99.8% with 91.8% of ethylene glycol selectivity. Byproducts produced in the form of diethylene glycol and triethylene glycol. In the process of ethylene oxide are needed as much 23,529.7386 kg/hour and as much water as 192,831.6709 kg/hour. The products produced in the form of ethylene glycol as 27,777.7778 kg/hour. Utilities include water provision process support for 720,341.4345 kg/h obtained from Tangerang Cisadane river water, the provision of saturated steam at 34827.955 kg/hour of fuel boiler using fuel oil in the form of 11,482.4919 L/hour for two boiler, electrical needs of 2,720.3 kW obtained from the PLN and a generator set as a backup. Plant design of ethylene glycol using a fixed capital of Rp 968,080,018,924,- and a working capital of Rp 1,809,340,555,217,-. Based on the economic analysis of the feasibility of establishing a factory, then the ethylene glycol plant is profitable and worth is established. Profits earned before taxes was Rp 655,476,883,524,- per year after taxes 30% profits reached Rp 458,763,818, 467,- per year. Percent Return On Investment (ROI) before tax after tax 67.70% and 47.39%. Pay Out Time (POT) before tax for 1.29 years and 1.7 years after tax. Break Even Point (BEP) of 48.5%, and Shut Down Point (SDP) amounted to 36.87%. Discounted Cash Flow (DCF) accounted for 25.87%.